VIOLÊNCIA OBSTÉTRICA NO BRASIL: : OFENSA VELADA À GARANTIA DO DIREITO À SAÚDE DAS MULHERES (REMUNOM, 2023)
Obstetric violence is a relevant problem in the national public health scenario, responsible for causing the violation of rights during processes involving childbirth. This violence can manifest itself in different ways, from misinformation and lack of informed consent to unnecessary and invasive procedures, jeopardizing women's access to humanized care that is compatible with the parturient's decisions. In addition, obstetric abuse contributes to the increase in maternal and child mortality, and to effectively combat this adversity, it is necessary to invest in public policies that guarantee access to quality and respectful humanitarian care, in addition to offering qualification and training to healthcare professionals. health, as well as asserting the right to information and informed consent.